Exploring the Antecedents to the Reputation of Chinese Public Sector Organizations During COVID-19: An Extension of Situational Crisis Communication Theory - Chunxia, Zhao; Fei, Wang; Wei, Fang (Frontiers in Psychology, 2022)
The study is intended to examine the impact of crisis responsibility on the reputation of the Chinese public sector organization during the COVID-19 crisis. In addition to that, the study has also examined the mediating role of crisis response strategy in the relationship between crisis responsibility and the reputation of the Chinese public sector organization during the COVID-19 crisis. Lastly, the study has also examined the moderating role of internal crisis communication in the relationship between the crisis responsibility and crisis response strategy of the Chinese public sector organization during COVID-19. This study bases on a quantitative research approach along with a cross-sectional research design. The population of the study is the Chinese public sector organization companies. Data is collected from the employees working in Chinese public sector organizations. The current study used 500 sample sizes; 205 valid responses are received which were used in data analysis. The SEM-PLS is used for the data analysis. The result of the study indicates that all the direct hypotheses are accepted significantly, which indicates that the crisis responsibility and crisis response strategy are significant determinants of organizational reputation during the COVID-19. In a similar vein, the crisis responsibility has placed a significant impact on the crisis response strategy of Chinese organizations during COVID-19. The study is among the pioneer studies on crisis responsibility in the Chinese public sector organization during COVID-19. The study has employed an extended framework encircling the literature on crisis responsibility, crisis response strategy, internal crisis communication, and organizational reputation. Theoretically, the study has extended the situational crisis communication theory framework by incorporating internal crisis communication in the framework.